The enemy on display : the Second World War in eastern European museums /: the Second World War in eastern European museums. (2015) - Bogumił, Zuzanna; Bogumił, Zuzanna; Wawrzyniak, Joanna, 1975-; Buchen, Tim; Ganzer, Christian; Senina, Maria
No abstract available